OVERWEIGHT AND OBESITY PREVALENCE IN YOUNG STUDENTS - Ramona Ancuța NUȚ; Paula Alina APOSTU (Cluj University Press, 2021)
Introduction. Globally, there is a growing prevalence of overweight and obesity in both developing and developed countries. Until recently, it was perceived that obesity mainly affects middle-aged adults. However, there is a growing trend towards obesity among young adults, especially university students. Objective. This study aims to assess the overweight and obesity prevalence and its related factors in a random sample of students selected from 10 faculties of "Babeș-Bolyai" University. Methods. This transverse study included a self-administered questionnaire and gathered anthropometric measurements. The population subject of study consisted in 1430 students, of which 694 (48.5%) men and 736 (51.5%) women, aged between 20 and 25 years, (69.4%) from urban environment and (30.6%) from rural environment. The body mass index (BMI) has been used for assessing the weight. Results. Amongst women, 64.4% had normal weight, 18.9% were overweight and 5.8% were obese, while amongst men 62.1% had normal weight, 14.1% were overweight and 5.2% were obese. Generally speaking 22% of participants were overweight or obese (24.7% women and 19.3% men). In multivariate regression in younger men coming from a region with higher incomes, conscientiously avoiding fats, alcohol and tobacco consumption, physical inactivity and in older women coming from a region with higher incomes, avoiding fats consumption, cholesterol and post-traumatic stress symptoms have been associated to overweight or obesity. Conclusions. The study found a high prevalence of overweight / obesity among university students. Several gender-specific health risk practices that can be used in health promotion programs have been identified. REZUMAT. Prevalența supraponderalității și obezității la tinerii studenți. Introducere. La nivel global, există o prevalență în creștere a supraponderalității și a obezității atât în țările în curs de dezvoltare, cât și în cele dezvoltate. Până de curând, s-a perceput că obezitatea afectează mai ales adulții de vârstă mijlocie. Cu toate acestea, devine evidentă o tendință de creștere constantă a obezității în rândul tinerilor adulți, în special studenți în cadrul universităților. Obiectivul. Acest studiu evaluează prevalența supraponderalității/obezității și a factorilor asociați acesteia în rândul unui eșantion aleatoriu de studenți din 10 facultăți din Universitatea "Babeș-Bolyai". Metode. Acest sondaj transversal a cuprins un chestionar autoadministrat și a colectat măsurători antropometrice. Populația studiată a fost de 1430 de studenți din care bărbați 694 (48,5%) și femei 736 (51,5%), cu vârste cuprinse între 20 și 25 de ani, proveniți din mediul urban (69,4%) și mediul rural (30,6%). Indicele de masă corporală (IMC) a fost utilizat pentru starea greutății. Rezultate. În rândul femeilor, greutatea normală a fost de 64,4%, supraponderalitatea 18,9% și obezitatea 5,8%, în timp ce în rândul bărbaților greutatea normală de 62,1%, supraponderalitatea 14,1% și obezitatea 5,2%. În general, 22% erau supraponderali sau obezi (24,7% femei și 19,3% bărbați). În regresia multivariată în rândul bărbaților, vârstă mai tânără, provenind dintr-o zonă cu venituri mai ridicate, evitând în mod conștient grăsimile și colesterolul, inactivitatea fizică, iar în rândul femeilor în vârstă, provenind dintr-o zonă cu venituri mai mari, evitarea grăsimilor și a colesterolului au fost asociate cu supraponderalitatea sau obezitatea. Concluzii. Studiul a constatat o prevalență ridicată a supraponderalității/obezității în rândul studenților universitari. Au fost identificate mai multe practici de risc pentru sănătate specifice genului care pot fi utilizate în programele de promovare a sănătății. Cuvinte cheie: obezitate, supraponderalitate, inactivitate fizică